(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2025)
This study aims to examine the impacts of various monetary services accessibility indicators on Algeria’s financial expansion from 2004 to 2020. The study utilized indicators such as the density of commercial bank branches and ATMs per 100,000 adults, the number of deposit accounts and borrowers per 1,000 adults, the total credit extended to the private sector, and the GDP growth rate to represent economic development. The research applied multiple linear regression analysis conducted with EVIEWS 12 software to evaluate various hypotheses. The findings indicated that the number of ATMs had a positive impact on financial expansion. In contrast, the number of deposit accounts and borrowers did not significantly affect economic progress. Additionally, the existence of commercial bank branches and the amount of credit extended to the private sector had a negative impact on financial expansion throughout the period studied. Keywords: Indicators, Accessibility of monetary services, Financial expansion, Multiple Linear Regression, Algeria.